Advancing cancer treatment: in vivo delivery of therapeutic small noncoding RNAs - Yang, Xiaoyue; Liang, Ying; Tong, Sheng (Frontiers in Molecular Biosciences, 2024)
In recent years, small non-coding RNAs (ncRNAs) have emerged as a new player in the realm of cancer therapeutics. Their unique capacity to directly modulate genetic networks and target oncogenes positions them as valuable complements to existing small-molecule drugs. Concurrently, the advancement of small ncRNA-based therapeutics has rekindled the pursuit of efficacious in vivo delivery strategies. In this review, we provide an overview of the most current clinical and preclinical studies in the field of small ncRNA-based cancer therapeutics. Furthermore, we shed light on the pivotal challenges hindering the successful translation of these promising therapies into clinical practice, with a specific focus on delivery methods, aiming to stimulate innovative approaches to address this foundational aspect of cancer treatment.